2009
DOI: 10.3928/08910162-20090916-01
|View full text |Cite
|
Sign up to set email alerts
|

Health and Gender Comparisons in the Long-Haul Trucking Industry

Abstract: This descriptive pilot study was conducted to determine whether health conditions and health care access differ between male and female long-haul truck drivers. Data indicated that 54% of men and 66% of women had a health care provider, but 21% of men and 35% of women had no health insurance. Male and female drivers both reported common health problems (e.g., back pain, sinus problems, hypertension, headaches, and arthritis). While working, drivers of each gender often waited until returning home to seek treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 9 publications
3
13
0
1
Order By: Relevance
“…Due to the nature of long-haul trucking, which takes and keeps drivers away from home for lengthy periods, truckers reported often delaying visits to their health care providers until they returned home. This finding is consistent with recent research on health conditions and health care access among long-haul truckers (Layne, Rogers, & Randolph, 2009). Health care could be provided in trucking settings such as truck stops.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Due to the nature of long-haul trucking, which takes and keeps drivers away from home for lengthy periods, truckers reported often delaying visits to their health care providers until they returned home. This finding is consistent with recent research on health conditions and health care access among long-haul truckers (Layne, Rogers, & Randolph, 2009). Health care could be provided in trucking settings such as truck stops.…”
Section: Discussionsupporting
confidence: 92%
“…Compounding these mental health problems is the fact that many of the over three million truck drivers in the US (US Department of Labor, Bureau of Labor Statistics, n.d.) have limited access to and utilization of health care while on the road (Layne, Rogers, & Randolph, 2009;Reed & Cronin, 2003;Stasko & Neale, 2007). Furthermore, the hyper-masculine work environment of truckers (Belzer, 2000;Ouellet, 1994;Stratford, Ellerbrock, Akins, & Hall, 2000) compounded by the Federal licensing regulations that require drivers to be "mentally fit" (Federal Motor Carrier Safety Administration, 2007;Federal Motor Carrier Safety Administration, 2008) are likely to be reasons for truckers to ignore or downplay any mental health problems they may experience.…”
mentioning
confidence: 99%
“…In light of the current body of knowledge regarding LHTD health behaviors and the influences of these behavioral patterns on subsequent health outcomes, these health promotion programs are important. For example, LHTDs are highly sedentary and engage in very little physical activity or exercise; they typically have unhealthy diets and are likely to consume large quantities of caffeine, tobacco, and other psychostimulants to counteract work-induced fatigue (Birdsey et al, 2015;Garbarino et al, 2017;Korelitz et al, 1993;Krueger, Belzer, et al, 2007;Layne, Rogers, & Randolph, 2009;McCallum, Sandquist, Mitler, & Krueger, 2003;Sieber et al, 2014;Turner & Reed, 2011;Wawzonek, 2016;Wenger, 2008). Unfortunately, few health promotion initiatives have targeted upper-level forces uniquely endemic to the LHTD profession that induce and constrain health-related behaviors -such as scheduling configurations, including long work hours and frequent shift work; poor sleep health; high job stress, including a fast pace of work and excessive time pressures; and workplace built environments described as healthyliving deserts Apostolopoulos, Peachey, & Sönmez, 2011;Apostolopoulos, Sönmez, Shattell, Gonzales, & Fehrenbacher, 2013;Apostolopoulos, Sönmez, Shattell, Haldeman, et al, 2011;de Pinho et al, 2006;Ebrahimi, Sadeghi, Dehghani, & Niiat, 2015;Garbarino et al, 2017;Guglielmi, Magnavita, & Garbarino, 2018;Lemke, Meissen, & Apostolopoulos, 2016;Shattell et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…to the overall truck driving population with an employer mix that includes private carriers, independent owner/operator drivers, and leased drivers for private carriers. (9, 15, 16, 20, 23, 43–48)…”
Section: Methodsmentioning
confidence: 99%
“…In spite of these required medical exams for licensure, commercial drivers have some of the highest rates of chronic diseases, occupational fatalities, and occupational injuries compared with other working populations. (1523) While there are relatively few studies that have examined the association between crash risk and multiple medical condtions among CMV drivers, some published data have indicated an increased crash risk among obese CMV drivers.,(24, 25) cardiovascular disease,(15, 16, 26, 27) diabetes,(28) medication use, (29, 30), and sleep apnea. (3133) One analysis reported that obese CMV drivers [body mass index (BMI) ≥ 30 kg/m 2 ] have a significantly higher crash rate (>2.0 times) than non-obese CMV drivers.…”
Section: Introductionmentioning
confidence: 99%